PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PENGEMBANGAN PRODUK OLAHAN BERBASIS KOMODITAS APEL DI DESA DUWET KABUPATEN MALANG - Yekie Senja Oktora; Ellyn Eka Wahyu (Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aimed to empower the community of Duwet Village, Tumpang District, Malang Regency, through the development of apple strudel as a local flagship product and village icon. The program was conducted based on the village’s high apple production potential, which had not been optimally processed into value-added products. The activities consisted of community needs assessment, technical training on apple processing, product packaging and branding, as well as digital marketing assistance. The program involved 16 participants, primarily housewives and young women, and was implemented at the Politeknik Negeri Malang bakery facility. The results showed that 70% of participants were able to independently produce apple strudel after the training, accompanied by improvements in packaging quality and market readiness. The branding of apple strudel as a local icon contributed to increased product attractiveness and income opportunities for the community. This program demonstrates that community empowerment through agricultural product processing can effectively enhance local economic resilience.